AWARENESS LEVEL AND BIOSECURITY COMPLIANCE OF EQUINE FARMERS AND OWNERS REGARDING EQUINE INFLUENZA IN KHYBER PAKHTUNKHWA, PAKISTAN - A. Khan; M. H. Mushtaq; M. U. D. Ahmad; J. Nazir; A. Rash; Z. Fatima; A. Khan; S. H. Farooqi (Journal of Animal and Plant Sciences, 2018)
Equine influenza remains a substantive threat to the equine industry and a deeply neglected area of research in Pakistan. To address this problem a cross-sectional study was conducted to explore the level of awareness and biosecurity compliance related to equine influenza among equine owners and farmers. 378 equine farmers and workers from four randomly selected districts of Northern Province (Khyber Pakhtunkhwa) were interviewed, irrespective of age and sex. Frequencies were used as outcome variables in the ordinal logistic regression statistical analysis. Variables on univariate analysis “having a P value of ≤0.2” were included in the Multivariate regression models built with manual stepwise approaches. Descriptive analysis of the data showed that 23% of the respondents had high awareness, 16% medium, and 27% low regarding equine influenza. “The majority of the respondent had” low biosecurity compliance. Amongst them, 43% had high, 19% medium, and 31% had “low biosecurity practices compliance”. The age and geographical locations of the respondents were found to be significantly associated with low levels of awareness and biosecurity compliance. The comparative odds of lower biosecurity compliance were recorded decreasing as age increases. The overall awareness and biosecurity compliance level was found unsatisfactory, major reasons were low literacy rate and lack of training regarding the management of equines.
Keywords: Equine influenza; biosecurity; ordinal logistic regression; Cross sectional; Pakistan